The economic burden to the public health system of treating non-viral injecting-related injury and disease in Australia (a cost of illness analysis) - Sweeney, R.; Conroy, A.; Dwyer, Robyn; Aitken, C. (Wiley-Blackwell Publishing Asia, 2009)
Objective: We estimated the cost to the public health system of treating Injecting-Related Injuries and Diseases (IRIDs) in the three most populous states in Australia in the 12 months over 2005/06. Methods: We conducted a cost of illness analysis from the perspective of the public health system. Costs of treating IRIDs in the community were estimated from health service utilisation surveys of injecting drug users and physicians (yielding data on Government subsidised physician visits, medicines prescribed and emergency department presentations). Data on admitted hospitalisations in public hospitals due to IRIDs were extracted from State Government databases. Appropriate costs were attached to all Government-borne services and prescriptions to estimate the total cost to the public health system of treating IRIDs in 2005/06 in Queensland, NSW and Victoria. Results: Our estimate of the cost to the public health system of treating IRIDs in Queensland, NSW and Victoria in 2005/06 was $20 million. Conclusion: IRIDs are an underrecognised harm resulting from injecting drug use, but the economic burden of IRIDs in Australia are non-negligible. Research is needed to identify cost effective programs to reduce the clinical and economic burden caused by IRIDs, particularly to reduce hospitalisations due to IRIDs. Implications: General practitioners, clinicians and other health workers need to be alert to IRIDs in their injecting drug user clients to prevent progression to more serious disease and consequent elevation of the associated economic costs. © 2009 The Authors.